Pengalaman Orang Tua Selama Perawatan Anak di Pediatric Intensive Care Unit (PICU) - Sri Hendrawati; Septa Permana; Nenden Nur Asriyani Maryam (SENTRI: Jurnal Riset Ilmiah, 2026)
Care for children in the Pediatric Intensive Care Unit (PICU) is a stressful experience not only for the child but also for parents. The complex PICU environment, the use of advanced medical equipment, and the child’s critical condition can affect parents’ emotional, psychological, and spiritual well-being. Therefore, a deep understanding of parents’ experiences during their child’s care in the PICU is essential as a foundation for implementing family-centered care (FCC). During PICU hospitalization, parents strive to balance anxiety and hope, with clear and empathetic communication from healthcare professionals identified as a primary support need. This study aimed to explore parents’ experiences during their child’s care in the PICU. A qualitative descriptive design was employed. The participants consisted of five parents (three mothers and two fathers) whose children were treated in the PICU. Data were collected through in-depth interviews and analyzed using thematic analysis. The analysis identified six main themes: strong emotional reactions when the child was first admitted to the PICU; parents’ feelings of role loss during the child’s hospitalization; nurses as a source of safety and reassurance; hope and spirituality as coping strategies; parents’ desire to be more involved in their child’s care; and unmet parental needs during PICU care, particularly related to information, emotional support, and orientation to PICU routines. Spirituality emerged as an important parental need within the Indonesian cultural context and played a significant role in parents’ coping processes. In conclusion, parents’ experiences during their child’s care in the PICU are complex and shaped by interactions with healthcare providers, fulfillment of informational needs, involvement in care, and emotional and spiritual support. These findings highlight the importance of implementing holistic and culturally sensitive family-centered care in PICU nursing practice.